2005
DOI: 10.1182/blood-2005-07-2781
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of spontaneous clearance of hepatitis C virus among people with hemophilia

Abstract: People with hemophilia were formerly at very high risk of infection with hepatitis C virus (HCV).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 39 publications
6
64
1
Order By: Relevance
“…Potential interactions between study site-categorized as the Baltimore Before and After Acute Study of Hepatitis (BBAASH; the study contributing largest number of reinfection events) versus other sites-and hypothesized predictors were evaluated. Hypothesized predictors were determined a priori on the basis of established predictors of primary clearance, including age [21], sex [1,15,22,23], IFNL4 genotype (SNP rs12979860; CC vs CT/TT) [24][25][26], the combined effect of sex and IFNL4 genotype (female rs12979860 CC vs others) [15,23], HCV genotype during reinfection (genotype 1 vs non-genotype 1) [15,27], and reinfection with the same versus a different HCV genotype from that in the primary infection. It was hypothesized that participants reinfected with the same HCV genotype would have a greater propensity toward reclearance [28,29].…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Potential interactions between study site-categorized as the Baltimore Before and After Acute Study of Hepatitis (BBAASH; the study contributing largest number of reinfection events) versus other sites-and hypothesized predictors were evaluated. Hypothesized predictors were determined a priori on the basis of established predictors of primary clearance, including age [21], sex [1,15,22,23], IFNL4 genotype (SNP rs12979860; CC vs CT/TT) [24][25][26], the combined effect of sex and IFNL4 genotype (female rs12979860 CC vs others) [15,23], HCV genotype during reinfection (genotype 1 vs non-genotype 1) [15,27], and reinfection with the same versus a different HCV genotype from that in the primary infection. It was hypothesized that participants reinfected with the same HCV genotype would have a greater propensity toward reclearance [28,29].…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Approximately 1.4 million deaths in 2001 were caused by chronic liver disease, of which 280,000 were attributed to HCV infection (Kim, 2002). It is estimated that some 20% of infected patients are able to spontaneously clear the virus (Zhang et al, 2006). A further 50%-60% of patients have a sustained response following antiviral treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a recent study that evaluated non-genetic factors in a cohort of hemophilic subjects has suggested that coinfection with hepatitis B, recent year at infection, and younger age at infection were associated with spontaneous viral clearance (15). In that study, no attempt was made to evaluate potential genetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Date of infection-The date of infection was estimated for all subjects based on their hemophilia type and severity and factor replacement histories, as has been previously described (15). For the current study, the date of infection was imputed as the midpoint between the exposure interval with the first use of factor concentrate defining the upper limit (MATLAB, MathWorks, Natick, MA).…”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation